Melatonin in the Regulation of Liver Steatosis following Prenatal Glucocorticoid Exposure. (13th April 2014) - Tiao, Mao-Meng; Huang, Li-Tung; Chen, Chih-Jen; Sheen, Jiunn-Ming; Tain, You-Lin; Chen, Chih-Cheng; Kuo, Ho-Chang; Huang, Ying-Hsien; Tang, Kuo-Shu; Chu, En-Wei; Yu, Hong-Ren
Abstract : Nonalcoholic fatty liver disease patients are characterized by hepatic steatosis. Prenatal glucocorticoid overexposure can result in steatosis. In this study, we aimed to determine the mechanism and cellular apoptosis of prenatal glucocorticoid overexposure in rats and whether melatonin can rescue the prenatal glucocorticoid-induced steatosis and apoptosis in neonatal rats. Pregnant Sprague-Dawley rats at gestational days 14 to 21 were administered dexamethasone. Acute effects of prenatal programming liver were assessed at postnatal day 7. The expression of proteins involved in the apoptotic and methylation pathways was analyzed by RT-PCR and Western blotting. Apoptosis and steatosis were examined by histology staining. The liver steatosis and apoptosis were increased in prenatal glucocorticoid group more than in control group and decreased in melatonin group. The expression of leptin decreased in prenatal glucocorticoid and increased in melatonin group by liver RT-PCR and Western blot study. Caspase 3, TNF- α proteins expression, and TUNEL stains increased in prenatal glucocorticoid compared with control and decreased in melatonin group. The liver histone deacetylase, DNA methyltransferase activity, and DNA methylation were increased in prenatal glucocorticoid and decreased in melatonin group. The present study showed that the prenatal glucocorticoid induced programming liver steatosis at day 7 after delivery, possibly via altered leptin expression. Melatonin can reverse the methylation of leptin and decreased liver steatosis.